Evaluation of Genetic Diversity among Different Melia composita CPTs using Random Amplified Polymorphic DNA (RAPD) Markers - Johar, Vishal; Dhillon, R. S.; Singhdoha, Amit (International Journal of Bio-resource and Stress Management, 2018)
The present study was conducted to evaluate the genetic diversity among different candidate plus trees (CPTs) of Melia composita for providing a wider base for the further improvement of this versatile short rotation tree species. RAPD molecular markers were used to evaluate the genetic diversity in populations of Melia composita Willd. (Burma dek) from different agroclimatic regions. Out of the 38 decamer primers used, 13 yielded polymorphic banding patterns. In total, 105 different bands were reproducibly obtained, out of which 69 (65.7%) were polymorphic. The polymorphisms were scored and used in band-sharing analysis to identify genetic relationships. Cluster analysis based on Jaccard’s similarity coefficient using UPGMA grouped all the 24 populations into two major groups. Similarity indices ranged from 0.80 to 0.91, indicating that Burma dek germplasm within India constitutes considerably narrow genetic base. The present study reveals that PCR based fingerprinting technique, RAPD; is informative for estimating the extent of genetic diversity as well as to determine the pattern of genetic relationships between different candidate plus trees (CPTs) of Melia composita with polymorphism levels sufficient to establish informative fingerprints with relatively fewer primer sets. Hence the study provides a basis for tree breeders to make informed choices on selection of parental material based on genetic diversity to help overcome some of the problems usually associated with a tree crop improvement program.